Ganoderic acid A protects neural cells against NO stress injury in vitro via stimulating β adrenergic receptors - Yu Zi-ru; Jia Wei-hua; Liu Chao; Wang Hong-qing; Yang Hai-guang; He Guo-rong; Chen Ruo-yun; Du Guan-hua (Acta Pharmacologica Sinica, 2020)
Excessive nitric oxide (NO) causes extensive damage to the nervous system, and the adrenergic system is disordered in many neuropsychiatric diseases. However, the role of the adrenergic system in protection of the nervous system against sodium nitroprusside (SNP) injury remains unclear. In this study, we investigated the effect of ganoderic acid A (GA A) against SNP injury in neural cells and the role of adrenergic receptors in GA A neuroprotection. We found that SNP (0.125−2mM) dose-dependently decreased the viability of both SH-SY5Y and PC12 cells and markedly increased NO contents. Pretreatment with GA A(10μM) signiﬁcantly attenuated SNP-induced cytotoxicity and NO increase in SH-SY5Y cells, but not in PC12 cells. Furthermore, pretreatment with GA A caused signiﬁcantly higher adrenaline content in SH-SY5Y cells than in PC12 cells. In order to elucidate the mechanism of GA A-protecting SH-SY5Y cells, we added adrenaline, phentolamine, metoprolol, or ICI 118551 1 h before GA A was added to the culture medium. We found that addition of adrenaline (10 μM) signiﬁcantly improved GA A protection in PC12 cells. The addition of β1-adrenergic receptor antagonist metoprolol (10 μM) or β2-adrenergic receptor antagonist ICI 118551 (0.1 μM) blocked the protective effect of GA A, whereas the addition of α-adrenergic receptor antagonist phentolamine (0.1 μM) did not affect GA A protection in SH-SY5Y cells. These results suggest that β-adrenergic receptors play an important role in the protection of GA A in SH-SY5Y cells against SNP injuries, and excessive adrenaline system activation caused great damage to the nervous system.